Strategic accountability for sustainability of natural resources – public discharge and optimism in sub-Saharan Africa - Asare, E.T.; Burton, B.; Dunne, T. (Emerald Publishing Limited, 2021)
Purpose – This study aims to explore individual perceptions about how the government, as the main architect of policies and regulations, discharges strategic accountability in Ghana’s oil and gas sector and, in so doing, promotes resource sustainability. Design/methodology/approach – The study reports on a series of interviews with key actors using institutional theory as a lens for discussion and interpretation of results. This approach forms the basis for a number of specific contributions to knowledge regarding strategic accountability around natural resource discoveries. Findings – Whilst many deeply-set problems appear to persist, the paper reports some favourable movement in public perceptions regarding institutional accountability that has not been identified previously. The empirical findings demonstrate how the three elements of institutional theory work together in an emerging country’s natural resource industry to drive a potentially holistic strategic institutional legitimacy, contrary to the existing pervasive picture of detrimental regulative, normative and cognitive institutionalism found within the region. Practical implications – The findings suggest that, contrary to existing regional evidence regarding institutional financial accountability practices around natural resources, Ghana has made favourable strides in terms of strategic accountability discharge. This discovery implies that with persistence and commitment, a meaningful degree of intelligent strategic accountability can be achieved and, with appropriate empirical methodology, identified and rationalised. Social implications – The persistent coercive pressure from the Ghanaian society that caused the government to listen to overtime and take positive steps in the institutionalisation of their strategic accountability process which translated into a holistic institutional legitimacy that has eluded the sub-region for decades, is a glimmer of hope for other societies within the sub-Saharan region that all is not lost. Originality/value – The paper suggests an empirically driven approach to understanding the institutionalisation of strategic accountability practices and their impact on sustainability around natural resources in sub-Saharan Africa. The focus on the strategic aspect of accountability – rather than the financial as in most prior work – and the consideration of opinions at more than a single point in time permits the identification of novel evidence regarding accountability in emerging economies.
Research Article
Keywords: Sustainability; Institutionalism; Ghana; Natural resources; Strategic accountability; Sub-Sahara